ANALISIS DAN PERANCANGAN SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT PADA PT PANCARAN ANEKA MOTOR - Elis Sondang (Jurnal Informatika dan Bisnis, 2012)
Information   and   communication   technology   is   growing   rapidly   nowadays.   Many companies  have  already  made  use  of  information  and  communication  technology  to support performance and achievement of corporate objectives. To meet the customer needs according to the mission of the company and improve company’s competitiveness, it is necessary to develop an effective customer relationship management system. The customer relationship management system developed should be able to fulfill company’s needs of acquiring new customers, enhancing customer profitability, and retaining the existing relationship. The research uses literature, interviews and direct observations on PT Pancaran Aneka Motor. Customer relationship management application is developed with the Visual Basic .NET based programming language. The result of the research is customer relationship management information system which aims to assist the company in acquiring new customers, enhancing customer relationship, and retaining it with customers’ information management, complaints management, complaint responses handling, service booking,  regular service reminder, and reports which are able to assist the management in decision making. The conclusion  obtained  from  this research  is  the customer  relationship  management system application provides the simplicity in conducting the customer relationship management process.